Bridging the gap: The moderating roles of institutional quality and compliance on the link between CSR and financial performance. (10th June 2023) - Bokhari, Syed Asad Abbas; Ali, Murad; Albort-Morant, Gema; Latan, Hengky; Lopes de Sousa Jabbour, Ana Beatriz; Ullah, Shakir; Salam, Mohammad Asif; Vo-Thanh, Tan
Abstract: Corporate social responsibility (CSR) is widely acknowledged to have a significant impact on firm's financial performance, but it is yet ambiguous how institutional, cultural and national factors influence this relationship in corruption contexts. Therefore, institutional mechanisms and perceived corruption should not be considered in isolation, as this would jeopardize the company's ability to act in a socially responsible manner. Obtaining an institutional approach of corruption and using self-administered survey data collected from 632 Pakistani firms operating in manufacturing and service sectors, we investigated the impact of CSR, institutional quality and law enforcement (IQLE), and internal compliance and ethical management (ICEM) on firm financial performance. Our results found that IQLE negatively moderates and weakened the positive relationship between CSR and firm financial performance. Additionally, we discover that ICEM positively moderates and strengthened the direct relationship between CSR and financial performance. We show that improving compliance and ethics management, CSR has the potential to enhance financial performance. Highlights: This research focuses on corporate social responsibility (CSR) and financial performance. We used longitudinal data on manufacturing and service firms listed on Pakistan stock exchange (PSE). Institutional quality and law enforcement (IQLE) weakened the relationship between CSR and financial performance. Internal compliance and ethical management (ICEM) strengthened the relationship between CSR and financial performance.